Analysis of Community Views on Correspondence in Manual Use - Nindya Azzahra; Andri Soemitra (Penerbit Jurnal Indonesia, 2022)
This study discusses the analysis of the views of the community towards correspondence in the use of manuals. This research use qualitative research methods. Qualitative methods used to answer research problems related to data in the form of narratives sourced from interviews, observations, document multiplication. The purpose of this research is to analyze how the manual view. However, the results obtained from this study are how the public’s perception of the quality of Correspondence in the Use of Manuals in Indonesia generally assesses that it is still not as expected, this can be seen, among others, from the number of complaints or complaints from the public at the Ministry of Defense such as regarding procedures and convoluted working mechanism, not transparent, less informative.